Quartz fiber joint glue based on methyl silicone oil and preparation method thereof

By using joint glue based on methyl silicone oil, the problems of insufficient bonding strength, slow penetration speed and toxicity of the existing quartz fiber joint glue are solved, and the non-toxic, low-cost, environmentally friendly and efficient bonding effect is achieved, ensuring the flatness and color difference of the product.

CN119505759APending Publication Date: 2025-02-25HENAN SHENJIU TIANHANG NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311031712.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-16
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing quartz fiber joint glue has problems such as insufficient adhesion, slow penetration, toxicity, high cost, pollution of the environment, endangering workers' health and leading to product color difference.

Method used

Using a joint glue based on methyl silicone oil, a colorless, transparent and viscous glue is formed through the combination of degluing agent, methyl silicone oil and polymethyl methacrylate molding powder, with significantly enhanced adhesion and permeability.

Benefits of technology

It realizes a non-toxic, low-cost, environmentally friendly, non-polluting the environment and does not endanger human health, enhances adhesion and permeability, avoids color difference problems, and has good surface flatness.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to quartz fiber joint glue based on methyl silicone oil and a preparation method thereof. The composition comprises the following substances: 60-85% of a dispergator, 4-12% of methyl silicone oil and 10-25% of polymethyl methacrylate molding powder, and the preparation method comprises the following steps: adding a set amount of the dispergator into a preparation barrel, and stirring; slowly adding a set amount of methyl silicone oil into the preparation barrel, and stirring for 5 minutes; and slowly adding a set amount of polymethyl methacrylate molding powder into the preparation barrel, and continuously stirring until the polymethyl methacrylate molding powder is completely dissolved, no white particles exist, and the solution is completely transparent and viscous. The adhesive has the advantages of no toxicity, small smell, simple and easily available formula, low cost, convenience in preparation and operation, no environmental pollution, no harm to human health, strong adhesion to quartz fiber yarns, high permeation speed, no hand sticking, good surface smoothness of the bonded quartz fiber product, no color difference at the bonded part after resin permeation compared with the color of quartz fiber, and no pollution to the environment. And the prepared composite material has no obvious color difference.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to methyl silicone oil-based quartz fiber joint glue and a preparation method thereof. Background Art

[0002] Quartz fiber is a woven material used for textile, weaving, and three-dimensional weaving. It can be made into quartz fiber yarn, which has high strength, high temperature resistance, heat insulation, electrical insulation, and good chemical stability. It has a wide range of applications in high temperature resistance, heat insulation, filtration, and flame retardancy. Quartz fiber yarn can be woven into quartz fiber cloth, belts, sleeves, etc., and can also be used as a reinforcing material for composite materials.

[0003] However, quartz fiber yarn also has the disadvantages of being brittle and not wear-resistant, especially during processing, it is easy to wear and break, which leads to yarn fuzzing and reduced strength. Therefore, quartz fiber yarn often breaks during processing, which requires the use of special joint glue to connect quartz fiber yarn.

[0004] However, the current quartz fiber factories, glass fiber factories and basalt fiber factories use traditional dibutyl phthalate type joint glue, which has a complex formula, high cost, and is toxic. It will pollute the environment and endanger the health of workers. More importantly, its bonding force is not very strong and the penetration speed is slow. The surface flatness of the quartz fiber bonded with it is poor, and there is color difference after bonding, especially after it is made into a composite material, there is color difference at the bonding point of the yarn, which affects the product quality.

[0005] On the other hand, dibutyl phthalate has been banned by the European Union because it has been identified as an environmental hormone that can cause cancer in animal liver tissue and disrupt the endocrine system. When it is subsequently incinerated, it will release large amounts of chlorine, vinyl chloride, dioxins and other toxic substances. Summary of the invention

[0006] The purpose of the present invention is to provide a quartz fiber joint glue based on methyl silicone oil, which is non-toxic, has strong bonding strength, fast penetration, low cost and good flatness; the purpose of the present invention is also to provide a preparation method of the above-mentioned quartz fiber joint glue based on methyl silicone oil.

[0007] In a first aspect, the present invention provides a quartz fiber joint glue based on methyl silicone oil, which adopts the following technical scheme: quartz fiber joint glue based on methyl silicone oil, wherein the joint glue is made of the following raw materials in percentage by mass: 60-85% of dissolving agent; Methyl silicone oil 4-12%; Polymethyl methacrylate molding powder 10-25%.

[0008] When the methyl silicone oil-based quartz fiber joint glue of the present invention is used to make joints of quartz fiber products, the methyl silicone oil can react physically and chemically with the polymethyl methacrylate molding powder, and under the dissolving action of the dissolving agent, a colorless and completely transparent viscous colloid is formed. The glue itself is non-toxic, does not pollute the environment, does not harm the health of workers, and the material is easy to obtain, and the cost is significantly reduced. Due to the completely colorless and transparent characteristics, the color of the bonded quartz fiber will not be increased or changed, so the quartz fiber products bonded by the glue have no color difference. Furthermore, due to the effective effect of the methyl silicone oil on the lubrication and softening of the polymethyl methacrylate molding powder, the overall bonding force of the glue is significantly enhanced, and the permeability is also significantly improved. At the same time, after the bonding is solidified, the surface of the product is very smooth and has good flatness. Moreover, if it is accidentally left on the hands, it is also very convenient to clean up due to its non-sticky characteristics.

[0009] Preferably, the methyl silicone oil is 201 methyl silicone oil. The polymethyl methacrylate molding powder is 613 polymethyl methacrylate molding powder.

[0010] Preferably, the viscosity of the dissolving agent is 2-5 cps, and the effective substance is ≥35%.

[0011] Preferably, the viscosity of the 201 methyl silicone oil is 100±8mm² / s, and contains 97-103% polymerized dimethylsiloxane.

[0012] Preferably, the 613 polymethyl methacrylate molding powder is in powder form, and the PMMA microsphere particle size is 250-300 mesh.

[0013] In the second aspect, the technical scheme of the preparation method of the quartz fiber joint glue based on methyl silicone oil of the present invention is as follows: Add a set amount of dissolving agent into the preparation barrel and stir; Slowly add the set amount of methyl silicone oil into the preparation barrel and stir for 5 minutes; Slowly add a set amount of polymethyl methacrylate molding powder into the preparation bucket and stir continuously until the polymethyl methacrylate molding powder is completely dissolved, no white particles are left, and the solution is completely transparent and viscous.

[0014] Compared with traditional joint glue, its preparation process is very simple, and because it is non-toxic and does not require closed operation, the operation is very convenient and fast, and the preparation efficiency is relatively high.

[0015] In summary, the present application has the following beneficial effects: non-toxic, low odor, simple and easy to obtain formula, low cost, convenient configuration and operation, no pollution to the environment, no harm to human health, strong adhesion to quartz fiber yarn, fast penetration speed, non-sticky, good surface smoothness of the bonded quartz fiber product, no color difference at the bonding point after resin penetration compared with the color of quartz fiber, and no obvious color difference after being made into a composite material. DETAILED DESCRIPTION

[0016] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, rather than all of the embodiments.

[0017] Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making any creative work shall fall within the scope of protection of the present invention.

[0018] It should be noted that relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0019] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0020] The corresponding disintegrator, 201 methyl silicone oil and 613 polymethyl methacrylate molding powder and other materials in the following examples can all be purchased commercially, wherein: When choosing a debonding agent, it is best to meet the following conditions: the viscosity of the debonding agent is 2-5cps, and the effective substance is ≥35%; the debonding agent (also known as debonding agent or debonding agent) is a synthetic chemical agent that can quickly, conveniently and effectively remove chemical components such as grease and glue, and play a role in cleaning the surface. The debonding agent is made by mixing turpentine, rosin water, 120# gasoline, kerosene, etc. The chemical components include: benzene, toluene, xylene, acetone, ethyl acetate, butyl acetate, ethanol, etc.

[0021] When choosing 201 methyl silicone oil, it is best to meet the following conditions: the viscosity of 201 methyl silicone oil is 100±8mm² / s, and it contains 97-103% polymerized dimethylsiloxane; polymerized dimethylsiloxane is non-toxic and odorless, has physiological inertness, good chemical stability, electrical insulation and weather resistance, good hydrophobicity, and high shear resistance, and can be used for a long time at -50℃~200℃; When choosing 613 polymethyl methacrylate molding powder, it is best to meet the following conditions: 613 polymethyl methacrylate molding powder is in powder form, and the PMMA microsphere particle size is 250-300 mesh. Polymethyl methacrylate molding powder is a powdery or granular homopolymer or copolymer with methyl methacrylate as the main raw material. It is also called organic glass molding compound. It is an important variety of organic glass.

[0022] Example 1 of the quartz fiber joint glue based on methyl silicone oil of the present invention: The quartz fiber joint glue based on methyl silicone oil of this embodiment is composed of the following components in terms of weight percentage: Glue dissolving agent 80%; 201 methyl silicone oil 8%; 613 polymethyl methacrylate molding powder 12%.

[0023] Prepare according to the following method: First, add the prepared and weighed amount of dissolving agent into the preparation bucket and start stirring; Slowly add the accurately weighed 201 methyl silicone oil into the preparation barrel and stir continuously for 5 minutes; Slowly add the 613 polymethyl methacrylate molding powder accurately weighed in proportion into the preparation barrel and stir continuously until the 613 polymethyl methacrylate molding powder is completely dissolved without white particles, and the solution is completely transparent and viscous, which becomes the required methyl silicone oil-based quartz fiber joint glue. Finally, fill the prepared joint glue into a sealed plastic barrel.

[0024] Test Example 1 using the methyl silicone oil-based quartz fiber joint glue of Example 1: The following specifications of quartz fiber yarn are selected as the test material, with a linear density of 72Tex, a diameter of 7.5μm, a twist of 50S, and a twisted yarn. The methyl silicone oil-based quartz fiber joint glue of Example 1 is used to perform joint bonding on the test material and for a period of time after bonding, and the following indicators are tested respectively: bonding strength, penetration speed, color difference, ease of operation, surface flatness, and the bonding between quartz fiber products and resin. The test results are as follows: Serial number Detection indicators unit standard Test Results 1 Bond Strength N / Tex ≥0.3 0.379 2 Penetration speed Second ≤8 6 3 Operational convenience point ≤1 0.7 4 Chromatic Aberration Compared with quartz fiber, there is no color difference at the bonding point after resin saturation conform to 5 Surface smoothness of quartz fiber products Smooth surface without protrusions conform to 6 Combination of quartz fiber products with resin No white silk, no delamination conform to From the above results, it can be seen that after using the glue of Example 1, the bonding strength of the product exceeds the standard, the penetration speed during the bonding process is less than the standard minimum value, the penetration speed is fast, and there is no white silk or delamination after bonding, which proves that the permeability is good, the bonding is good, the surface is flat and has no protrusions, which proves that the flatness is good.

[0025] Example 2 of the quartz fiber joint glue based on methyl silicone oil of the present invention: The quartz fiber joint glue based on methyl silicone oil of this embodiment is composed of the following components in terms of weight percentage: Glue dissolving agent 73%; 201 methyl silicone oil 12%; 613 polymethyl methacrylate molding powder 15%.

[0026] Prepare according to the following method: First, add the prepared and weighed amount of dissolving agent into the preparation bucket and start stirring; Slowly add the accurately weighed 201 methyl silicone oil into the preparation barrel and stir continuously for 5 minutes; Slowly add the 613 polymethyl methacrylate molding powder accurately weighed in proportion into the preparation barrel and stir continuously until the 613 polymethyl methacrylate molding powder is completely dissolved without white particles, and the solution is completely transparent and viscous, which becomes the required methyl silicone oil-based quartz fiber joint glue. Finally, fill the prepared joint glue into a sealed plastic barrel.

[0027] Test Example 2 using the methyl silicone oil-based quartz fiber joint glue of Example 2: The following specifications of quartz fiber yarn were selected as the test material, with a linear density of 72Tex, a diameter of 7.5μm, a twist of 50S, and twisted yarn. The methyl silicone oil-based quartz fiber joint glue of Example 2 was used to perform joint bonding on the test material and for a period of time after bonding, and the following indicators were tested respectively: bonding strength, penetration speed, color difference, ease of operation, surface flatness, and the bonding between quartz fiber products and resin. The test results are as follows: Serial number Detection indicators unit standard Test Results 1 Bond Strength N / Tex ≥0.3 0.412 2 Penetration speed Second ≤8 7 3 Operational convenience point ≤1 0.61 4 Chromatic Aberration Compared with quartz fiber, there is no color difference at the bonding point after resin saturation conform to 5 Surface smoothness of quartz fiber products Smooth surface without protrusions conform to 6 Combination of quartz fiber products with resin No white silk, no delamination conform to From the above results, it can be seen that after using the glue of Example 2, the bonding strength of the product exceeds the standard, the penetration rate during the bonding process is less than the standard minimum value, the penetration rate is fast, and there is no white silk or delamination after bonding, which proves that the permeability is good, the bonding is good, the surface is flat and has no protrusions, which proves that the flatness is good.

[0028] Example 3 of the quartz fiber joint glue based on methyl silicone oil of the present invention: The quartz fiber joint glue based on methyl silicone oil of this embodiment is composed of the following components in terms of weight percentage: Glue dissolving agent 74%; 201 methyl silicone oil 6%; 613 polymethyl methacrylate molding powder 20%.

[0029] Prepare according to the following method: First, add the prepared and weighed amount of dissolving agent into the preparation bucket and start stirring; Slowly add the accurately weighed 201 methyl silicone oil into the preparation barrel and stir continuously for 5 minutes; Slowly add the 613 polymethyl methacrylate molding powder accurately weighed in proportion into the preparation barrel and stir continuously until the 613 polymethyl methacrylate molding powder is completely dissolved without white particles, and the solution is completely transparent and viscous, which becomes the required methyl silicone oil-based quartz fiber joint glue. Finally, fill the prepared joint glue into a sealed plastic barrel.

[0030] Test Example 3 using the methyl silicone oil-based quartz fiber joint glue of Example 3: The following specifications of quartz fiber yarn were selected as the test material, with a linear density of 72Tex, a diameter of 7.5μm, a twist of 50S, and twisted yarn. The methyl silicone oil-based quartz fiber joint glue of Example 3 was used to perform joint bonding on the test material and for a period of time after bonding, and the following indicators were tested respectively: bonding strength, penetration speed, color difference, ease of operation, surface flatness, and the bonding between quartz fiber products and resin. The test results are as follows: Serial number Detection indicators unit standard Test Results 1 Bond Strength N / Tex ≥0.3 0.351 2 Penetration speed Second ≤8 5.6 3 Operational convenience point ≤1 0.8 4 Chromatic Aberration Compared with quartz fiber, there is no color difference at the bonding point after resin saturation conform to 5 Surface smoothness of quartz fiber products Smooth surface without protrusions conform to 6 Combination of quartz fiber products with resin No white silk, no delamination conform to From the above results, it can be seen that after using the glue of Example 3, the bonding strength of the product exceeds the standard, the penetration speed during the bonding process is less than the standard minimum value, the penetration speed is fast, and there is no white silk or delamination after bonding, which proves that the permeability is good, the bonding is good, the surface is flat and has no protrusions, which proves that the flatness is good.

[0031] In other embodiments, 201 methyl silicone oil may be replaced by other brands of methyl silicone oil, and 613 polymethyl methacrylate molding powder may be replaced by other brands of polymethyl methacrylate molding powder.

[0032] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. The patent protection scope of the present invention shall be based on the claims. All equivalent structural changes made using the contents of the specification of the present invention should also be included in the protection scope of the present invention.

Claims

1. Quartz fiber joint glue based on methyl silicone oil, characterized in that: The joint glue is prepared from the following raw materials in percentage by mass: 60-85% of dissolving agent; Methyl silicone oil 4-12%; Polymethyl methacrylate molding powder 10-25%.

2. The quartz fiber joint glue based on methyl silicone oil according to claim 1, characterized in that: The methyl silicone oil is 201 methyl silicone oil.

3. The quartz fiber joint glue based on methyl silicone oil according to claim 1, characterized in that: The polymethyl methacrylate molding powder is 613 polymethyl methacrylate molding powder.

4. The quartz fiber joint glue based on methyl silicone oil according to claim 1, characterized in that: The viscosity of the dissolving agent is 2-5 cps, and the effective substance is ≥35%.

5. The quartz fiber joint glue based on methyl silicone oil according to claim 2, characterized in that: The viscosity of the 201 methyl silicone oil is 100±8mm² / s, and contains 97-103% polymerized dimethylsiloxane.

6. The quartz fiber joint glue based on methyl silicone oil according to claim 3, characterized in that: The 613 polymethyl methacrylate molding powder is in powder form, and the PMMA microsphere particle size is 250-300 meshes.

7. The method for preparing the quartz fiber joint glue based on methyl silicone oil according to any one of claims 1 to 6, characterized in that: Follow these steps: Add a set amount of dissolving agent into the preparation barrel and stir; Slowly add the set amount of methyl silicone oil into the preparation barrel and stir for 5 minutes; Slowly add a set amount of polymethyl methacrylate molding powder into the preparation bucket and stir continuously until the polymethyl methacrylate molding powder is completely dissolved, no white particles are left, and the solution is completely transparent and viscous.